Biological therapy of seropositive juvenile idiopathic arthritis: Results of a retrospective single-center study - M. I. Kaleda; Z. A. Kolkhidova; I. P. Nikishina (Научно-практическая ревматология)
Seropositive juvenile idiopathic arthritis (JIA) is one of the rarest and most unfavorable subtypes of juvenile arthritis, characterized by an increased frequency of inefficacy of therapy. Objective – to characterize biologic therapy in patients with seropositive JIA, to identify factors influencing the choice of a biological agents (BA) and the need to replace it, to evaluate the value of the JADI damage index for predicting the response to BA.Material and methods. The diagnosis of seropositive JIA for the period from 2010 to 2022 was verified in 92 patients, 10.9% were boys. The median age of JIA onset in the study group was 12.0 [7.7; 14.0] years. BA were prescribed to 89.1% of patients in the study group, 31.7% of them for a period of less than 1 year from the onset. The median number of active joints at the time of BA initiation was 15 [10; 22], median ESR – 29 [18; 43] mm/h, CRP – 15.0 [5.3; 31.0] mg/l. Extra-articular manifestations at the time of prescribing BA occurred in 29.0% of patients. The analysis of factors that could influence the need to switch BA was carried out: age of onset, timing of diagnosis verification and initiation of BA, gender, the number of active joints at the start of BA, ACCP positivity, RF, ACCP, ESR and CRP values – at the time of BA appointment, the presence of secondary Sjögren’s syndrome. Since 2021, the complex of examinations included the calculation of the JADI (The Juvenile Arthritis Damage Index) damage index in all patients from the study group who were admitted to the hospital (28 in total; 17.9% – boys). The median age of JIA onset among them was 10.5 [6.31; 13.0] years, 81.2% received BA. The JADI index was compared with the ACCP, RF, CRP, ESR and the need to prescribe and switch BA. The design of the study was a retrospective, open-label, non-randomized, uncontrolled study. Results. In the study group of patients, 29% had experience with more than 1 BA. Abatacept (45.1%), TNF-inhibitors (40.3%) were most often used as the first BA; tocilizumab and rituximab were predominantly used in the 2nd–4th line of therapy, with a trend towards their more frequent prescription in recent years. The main reason for switching from one BA to another is the secondary failure of therapy, 4.9% of patients have serious adverse reactions (AE). In general, AEs that did not require discontinuation of therapy were recorded in 24.6% of patients. Patients who received more than 1 BA had relatively higher values of RF, ACCP and significantly higher CRP. The mean value of JADI-A was 2.39 points, 50% of patients had significant JADI-A scores, 92.8% of whom received BA with experience of more than 1 prescription of BA in 28.6% of them. A direct correlation of the JADI index with ACCP, ESR and CRP was revealed. Conclusions. Seropositive JIA is characterized by a high need for prescribing BA, the frequency of prescribing BA is associated with significant indicators of the JADI damage index. The choice of a specific BA is determined, first of all, by the presence of systemic manifestations or secondary Sjögren’s syndrome. In patients with high surrogate measures of activity (especially CRP), given the high risk of secondary failure of TNF-inhibitors, tocilizumab in the first line of therapy may be considered as the preferred choice. Our data did not reveal an effect of ACCP positivity on the preferred choice or frequency of BA replacement. Attention was drawn to the trend towards higher RF and ACCP values in patients treated with more than one BA. A correlation was established between the JADI index and ACCP, ESR, and CRP, which indirectly leads to the conclusion that it is necessary to prescribe BA earlier in this category of patients in order to avoid permanent damage and increase the effectiveness of thera py. The use of BA had an acceptable safety profile.